The Effect of Water Application Levels on the Nutritional Value of Maize (Zea mays L.) Forage under Biochar-Amended Vertisol Soil in Kupang Regency, East Nusa Tenggara - Masria Masria; Maria Klara Salli; Magfira Syarifuddin; Cokorda Bagus Dharma Putra Mahardika; Jemseng Charles Abineno (The University of Lampung, 2025)
This study aimed to examine the effect of different water levels on the growth and nutritional value of maize (Zea mays L.) forage grown on Vertisol soil amended with corncob biochar. The research was conducted in Oesao Village, Kupang Regency, East Nusa Tenggara. Biochar was produced by pyrolyzing corncobs at 300–600 °C and applied in the soil at 6% by weight. The experiment used a Completely Randomized Design with four water levels (K1 = 100%, K2 = 90%, K3 = 80%, K4 = 70% of field capacity) and six replications for measuring plant growth. Soil property and proximate analyses were conducted using composite samples with three replications. Chemical properties of biochar, initial and post-treatment soil properties, plant growth (height, number, and leaf area), and forage nutritional quality were analyzed. The results showed that treatment K4 improved soil chemical properties including organic carbon, P₂O₅, cation exchange capacity (CEC), and exchangeable cations. Treatment K1 produced the best vegetative growth with the most leaves, leaf area, and plant height. Meanwhile, treatment K3 resulted in the best forage nutritional quality, with the highest nitrogen, crude protein, and crude fat content and the lowest crude fiber content. Overall, treatment K3 was considered the most optimal because it balanced plant productivity and forage quality.